A Bio‐Inspired Switch Based on Cobalt(II) Disulfide/Cobalt(III) Thiolate Interconversion1. Issue 21 (9th April 2014) - Gennari, Marcello; Gerey, Bertrand; Hall, Nikita; Pécaut, Jacques; Collomb, Marie‐Noëlle; Rouzières, Mathieu; Clérac, Rodolphe; Orio, Maylis; Duboc, Carole
Abstract Disulfide/thiolate interconversion supported by transition‐metal ions is proposed to be implicated in fundamental biological processes, such as the transport of metal ions or the regulation of the production of reactive oxygen species. We report herein a mononuclear dithiolate CoIII complex, [CoIIILS(Cl)] (1; LS=sulfur containing ligand), that undergoes a clean, fast, quantitative and reversible CoII disulfide/CoIII thiolate interconversion mediated by a chloride anion. The removal of Cl− from the CoIII complex leads to the formation of a bis(μ‐thiolato) μ‐disulfido dicobalt(II) complex, [Co2II, IILSSL]2+ (22+). The structures of both complexes have been resolved by single‐crystal X‐ray diffraction; their magnetic, spectroscopic, and redox properties investigated together with DFT calculations. This system is a unique example of metal‐based switchable Mn2‐RSSR/2 M(n+1)‐SR (M=metal ion, n=oxidation state) system that does not contain copper, acts under aerobic conditions, and involves systems with different nuclearities.